PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DENGAN TEKNIK NOMINAL GROUP UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 029 SUNGAIPINANG KECAMATAN TAMBANG KABUPATEN KAMPAR - Resuari, Mutiara Ardana; Alim, Jesi Alexander; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACT : The problem in this study is the low mathematics learning outcomes 029 fourth grade students of SDN Sungaipinang District of mine. This is caused by (1) the teacher did not apply the model / strategies in the learning process, (2) the teacher does not involve students in the learning process, (3) the teacher does not use the media time learning process. It can be seen symptoms include (1) the student is not able to complete the tasks set by the teacher, (2) students do not want / are afraid to ask, (3) the student is not able to develop his ideas, (4) in a group of only a few students working. It is necessary for the study of learning with the application of the learning model with the nominal group technique. In a study with the application of cooperative learning model with the nominal group technique, students are required to think themselves in solving the problems so that students can provide the best answer without any influence from other people's thinking. The study is in the form of Classroom Action Research (CAR). This study aims to improve mathematics learning outcomes 029 fourth grade students of SDN Sungaipinang Mining District of Kampar district. The results of this study indicate that cooperative learning model with nominal group technique can improve students' mathematics learning outcomes, namely an increase in the activity of the teacher and student activities. In the first cycle of teacher activity with an average 68,75% increase in cycle II to 83,75%, while the activity of students in the first cycle an average of 67,5% increased by 89,25% in the second cycle. Then, in the classical mastery learning in the first cycle is of 18 students, 10 (55,55%) students who completed, the second cycle increased to 15 (83,33%) students who completed. On improving student learning outcomes before the procedure, namely the average of 51,66, while the average student learning outcomes after the action is increased at the end of the first cycle replicates (59,72) and then increased in the second cycle (75,27). This means that the application of Cooperative Learning Model with Nominal Group Technique to Improve Student Learning Outcomes Math.Keywords : Cooperative Learning With Nominal Group Technique, Results Learning Mathematics